Using Stanford’s Design Thinking Model at the Rural Village Level - Lane, Paul; Christopher , KC (Advances in Social Sciences Research Journal, 2020)
A case history of a rural workshop using the Stanford Design Thinking Model in a -remote part of the Rio San Juan Nicaragua. The program is run under UNICAM UNAN-Managua believed to be the largest program of its kind. It is a chance to see how both facilitators and participants can learn in very simple settings. It is a chance to understand what kinds of things are impacting the lives of rural people in their quest for the basics of existence such as food and water. Most of all it is a living action of the dream of bringing top level education to the rural people of Nicargua. All the action takes place in a simple rancho at the edge of the Rio San Juan where participants come by canoe, and by foot.